2023
DOI: 10.1111/nep.14192
|View full text |Cite
|
Sign up to set email alerts
|

Financial toxicity experienced by rural Australian families with chronic kidney disease

Abstract: Aim: Chronic kidney disease (CKD) and its treatment places a financial burden on healthcare systems and households worldwide, yet little is known of its financial impact, on those who reside in rural settings. We aimed to quantify the financial impacts and out-of-pocket expenditure experienced by adult rural patients with CKD in Australia.Methods: A web based structured survey was completed between November 2020 and January 2021. English speaking participants over 18 years of age, diagnosed with CKD stages 3-5… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 9 publications
(2 citation statements)
references
References 52 publications
0
2
0
Order By: Relevance
“…Financial toxicity perpetuates socially determined barriers to healthcare [18] and it is likely to be more acute in low and low-middle income countries. Scholes-Robertson et al found that 78% of those living with CKD in Australian rural areas (>50 km from specialist kidney services) experienced financial hardship mostly due to cost of transport, medications and nephrologist fees [19], which raises equity concerns even in a high-income country with universal healthcare.…”
Section: Financial Statusmentioning
confidence: 99%
“…Financial toxicity perpetuates socially determined barriers to healthcare [18] and it is likely to be more acute in low and low-middle income countries. Scholes-Robertson et al found that 78% of those living with CKD in Australian rural areas (>50 km from specialist kidney services) experienced financial hardship mostly due to cost of transport, medications and nephrologist fees [19], which raises equity concerns even in a high-income country with universal healthcare.…”
Section: Financial Statusmentioning
confidence: 99%
“…People living in rural and remote Australia experience greater socioeconomic disadvantage, reduced access to primary health care, reduced availability and access to public infrastructure (transport and health services) and face geographical barriers that contribute to delayed referral to kidney specialist services and poorer health outcomes [135,136]. These patients experience high levels of financial insecurity related to managing CKD with and mean quarterly cost of AUS 308 (range AUS 0-4,000) for transportation and AUD 240 (range AUD 0-AUD 2,000) for medications accounting for the greatest out-of-pocket costs [137]. People living in rural and remote areas are also more likely to have lower levels of health literacy than urban counterparts [138][139][140], which may impact their understanding of CKD and treatment strategies [135].…”
Section: Quality and Equity In Ckd Care In Indiamentioning
confidence: 99%